2011
DOI: 10.1371/journal.pone.0023945
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Oxidase Subunit 4-Mediated Reactive Oxygen Species Contribute to Cycling Hypoxia-Promoted Tumor Progression in Glioblastoma Multiforme

Abstract: BackgroundCycling and chronic tumor hypoxia are involved in tumor development and growth. However, the impact of cycling hypoxia and its molecular mechanism on glioblastoma multiforme (GBM) progression remain unclear.MethodologyGlioblastoma cell lines, GBM8401 and U87, and their xenografts were exposed to cycling hypoxic stress in vitro and in vivo. Reactive oxygen species (ROS) production in glioblastoma cells and xenografts was assayed by in vitro ROS analysis and in vivo molecular imaging studies. NADPH oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
98
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(101 citation statements)
references
References 39 publications
0
98
1
Order By: Relevance
“…This response can be elicited by hypoxia itself; however, there is increasing evidence that ROS are able to potentiate the response. Increased ROS level and increased NOX4 expression have been observed in glioblastoma cell lines under hypoxic condition, and it has been suggested that NOX4-generated ROS promote the activation of HIF-1 and of glioblastoma progression (73).…”
Section: Nox In Cns Tumorsmentioning
confidence: 99%
“…This response can be elicited by hypoxia itself; however, there is increasing evidence that ROS are able to potentiate the response. Increased ROS level and increased NOX4 expression have been observed in glioblastoma cell lines under hypoxic condition, and it has been suggested that NOX4-generated ROS promote the activation of HIF-1 and of glioblastoma progression (73).…”
Section: Nox In Cns Tumorsmentioning
confidence: 99%
“…To mimic the clinical setting, we sought to test the efficacy of TAT-Lp15 when added to standard-of-care treatment with radiation plus temozolomide. BLI was utilized to assess intracranial tumor growth in the orthotopic GBM8401/SFFVLucGFP xenograft model (16,17,21). Consistent with the in vitro studies, mice that had TAT-Lp15 treatment before initiation of the combination of temozolomide and radiation treatment had significantly better tumor growth delay and survival rate than those pretreated with TAT-K22 or vehicle (Fig.…”
Section: Livin Blockage Enhances the Efficiency Of Radiation Plus Temmentioning
confidence: 60%
“…Here, we first demonstrate that the tumor microenvironment mediated expression pattern of Livin. To directly distinguish and isolate hypoxic tumor subpopulations from solid tumors, we used a reliable protocol of cycling-and chronic-hypoxic cell identification derived from our previous studies that allows subsequent immunofluorescence imaging and flow-cytometric analysis of the biosignature of these cells (16). Our results indicate that both of probable cycling and chronic hypoxic areas are important in tumor microenvironment-mediated Livin induction.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Nox4 is known as a dominant isoform of Nox family in glioblastoma tissues and cell lines, and its expression is increased under hypoxic stress [19,24,25]. Semi-quantitative RT-PCR analysis showed that Nox4 mRNA level was increased in hypoxia exposed U87 and U373 cells, while detectable change of Nox1, Nox2 and Nox5 mRNA was not observed under hypoxic stress (Fig.…”
Section: Nox4 Expression Is Increased In Hypoxic Glioblastomamentioning
confidence: 92%